JONATHAN EDWARDS AROUND THE WORLD (Jonathan Edwards studies, 2014)
This journal issue concludes with updates that were received from directors of various affiliated Jonathan Edwards Centers around the world at the date of this journal publication, and we thought our readers might be interested in reading them.